EFFECTS OF SPATIAL ARRANGEMENT AND POPULATION DENSITY ON GROWTH AND YIELD OF SESAME (SESAMUM INDICUM L.) IN SESAME/MAIZE INTERCROP - Ade Isaac, Afe (Journal of Agricultural Sciences (Belgrade), 2020)
Abstract: A field trial was carried out to investigate the growth and yield of sesame as affected by row arrangement and population density of component maize. Full population of sesame in two-row arrangements (1:1) and (2:2) were combined with four population densities of maize Viz: 100S: 100M; 100S: 75M; 100S: 50M and 100S: 25M (where S and M represented sesame and maize respectively). Sole crops each of sesame and maize at full population were included in the treatments as control. The treatments were arranged as 2x4 factorial combinations randomly arranged in split plot fashion and replicated three times. The spatial arrangement constitutes the main plots, while the population density was assigned to the subplot treatments. The number of pods per plant (NPP), length of fruit zone (LFZ), and yield of sesame were significantly (P≤0.5) influenced by the interactive effect of population ratios and row arrangement. All parameters measured in maize were influenced by population density and row arrangement except, number of cobs per plant (NCP), cob length (CL), and cob circumference (CC). Regardless of spatial arrangement and population density, aggressivity (A) value was positive for sesame and negative for maize. The competitive ratio (CR) values were also higher in sesame than maize. Based on land equivalent ratios (LER) and land equivalent coefficient (LEC) values, all population ratios tested indicated intercropping advantage with the highest value recorded at a full population of sesame mixed with fifty percent population of maize in a 2: 2-row arrangement and hence, recommended in a maize/sesame mixture.